(untitled) (Research, Society and Development, 2021)
Snakebite is an important public health problem because of its incidence, morbidity, and mortality. It may be related to climatic factors and rural habits. Snakes of the genus Bothrops are responsible for most snakebites in Brazil. The venom of these snakes has peculiar characteristics, with important proteolytic, coagulant, and hemorrhagic actions, leading to local and systemic alterations. Initial manifestations include local tissue injury, pain, swelling, bleeding, and bullous lesions that can progress to abscesses or tissue necrosis. Systemic manifestations should be carefully evaluated especially for the probability of hemorrhagic events such as epistaxis, gingivorrhagia, hematuria, and hemoptysis. Knowing the clinical manifestations of snakebites, as well as the adequate treatment, is essential. Efficient and rapid diagnosis can minimize victims’ injuries and the probability of death. The present study reports the clinical case of bleeding at a distant site from the initial site of venom inoculation after bite by a Bothrops snake, emphasizing the therapeutic approach and differential diagnosis in these cases.